2022
DOI: 10.1039/d2nj02011d
|View full text |Cite
|
Sign up to set email alerts
|

Substituted pyrrolyl-cyanopyridines on the platform of acylethynylpyrroles via their 1 : 2 annulation with acetonitrile under the action of lithium metal

Abstract: A facile one-pot synthesis of 2-(pyrrolyl)-4-aryl(hetaryl)-5-cyano-6-methylpyridines in 63–87% yield via the cyclization of available acylethynylpyrroles with two molecules of acetonitrile under the action of lithium metal at room temperature has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Also, it was reported that CH 2 CN − anion was added to ketones to form tertiary cyanomethyl alcohols [ 46 , 47 , 48 , 49 ]. Correspondingly, in the previous communication, we have shown that the intermediate propargyl alcohol 3 are actually adducts of acylethynylpyrroles and CH 2 CN − anion [ 36 ].…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Also, it was reported that CH 2 CN − anion was added to ketones to form tertiary cyanomethyl alcohols [ 46 , 47 , 48 , 49 ]. Correspondingly, in the previous communication, we have shown that the intermediate propargyl alcohol 3 are actually adducts of acylethynylpyrroles and CH 2 CN − anion [ 36 ].…”
Section: Resultsmentioning
confidence: 73%
“…The major product, in this case, became tertiary propargylic alcohol 3a (content in the reaction mixture was 78%). Pyrrolylpyridine 2a , previously a major product [ 36 ], was also present in the reaction mixture but in a much smaller amount (10%). Almost the same results were obtained in the presence of 2 eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our assumption that one of the stages in the assembly of the aniline ring is the addition of acetonitrile to the carbonyl group, as we recently showed on the example of the formation of pyridines from acylethynylpyrroles [ 73 ], was not confirmed: when the reaction of acylethynylpyrrole 1d with malononitrile was carried out without acetonitrile in THF, the yield of pyrrole 3d was 38%.…”
Section: Resultsmentioning
confidence: 94%